Auditory Feedback Assists Post hoc Error Correction of Temporal Reproduction, and Perception of Self-Produced Time Intervals in Subsecond Range - Mitani, Keita; Kashino, Makio (Frontiers in Psychology, 2018)
We examined whether auditory feedback assists the post-hoc error correction of temporal reproduction, and the perception of self-produced time intervals in the subsecond and suprasecond ranges. Here, we employed a temporal reproduction task with a single motor response at a point in time with and without auditory feedback. This task limits participants to reducing errors by employing auditory feedback in a post-hoc manner. Additionally, the participants were asked to judge the self-produced timing in this task. The results showed that, in the presence of auditory feedback, the participants exhibited smaller variability and bias in terms of temporal reproduction and the perception of self-produced time intervals in the subsecond range but not in the suprasecond range. Furthermore, in the presence of auditory feedback, the positive serial dependency of temporal reproduction, which is the tendency of reproduced intervals to be similar to those in adjacent trials, was reduced in the subsecond range but not in the suprasecond range. These results suggest that auditory feedback assists the post-hoc error correction of temporal reproduction, and the perception of self-produced time intervals in the subsecond range.